Fine Mapping of the Leaf Rust Resistance Gene Lr65 in Spelt Wheat ‘Altgold’ - Zhang, Qiang; Wei, Wenxin; Zuansun, Xiangxi; Zhang, Shengnan; Wang, Chen; Liu, Nannan; Qiu, Lina; Wang, Weidong; Guo, Weilong; Ma, Jun; Peng, Huiru; Hu, Zhaorong; et al. (Frontiers in Plant Science, 2021)
Wheat leaf rust (also known as brown rust), caused by the fungal pathogen Puccinia triticina Erikss. (Pt), is one by far the most troublesome wheat disease worldwide. The exploitation of resistance genes has long been considered as the most effective and sustainable method to control leaf rust in wheat production. Previously the leaf rust resistance gene Lr65 has been mapped to the distal end of chromosome arm 2AS linked to molecular marker Xbarc212. In this study, Lr65 was delimited to a 0.8 cM interval between flanking markers Alt-64 and AltID-11, by employing two larger segregating populations obtained from crosses of the resistant parent Altgold Rotkorn (ARK) with the susceptible parents Xuezao and Chinese Spring (CS), respectively. 24 individuals from 622 F2 plants of crosses between ARK and CS were obtained that showed the recombination between Lr65 gene and the flanking markers Alt-64 and AltID-11. With the aid of the Chinese spring reference genome sequence (IWGSC RefSeq v1.0), one SSR marker was developed between the interval matched to the Lr65-flanking marker and a high-resolution genetic linkage map was constructed. The Lr65 was finally located to a region corresponding to 60.11 Kb of the Chinese spring reference genome. The high-resolution genetic linkage map founded a solid foundation for the map-based cloning of Lr65 and the co-segregating marker will facilitate the marker-assisted selection of the target gene.